The Characteristic of Overhang Object to Material Usage on FDM 3D Printing Technology - Redyarsa Dharma Bintara; Aminnudin Aminnudin; Dani Prasetiyo; Ferian Rizki Arbianto (Journal of Mechanical Engineering Science and Technology (JMEST), 2019)
Fuse Deposition Modeling (FDM) 3D printing is one of additive manufacturing technology which physical 3D model is build up layer by layer. The support structure is almost involved on the process if overhang shape is met on the 3D model. It has main function to prevent the 3D printed model from collapsing. Commonly, the single material source of FDM 3D printer machine is to supply building two structure, structure of main 3D object and support structure. Hence, our goal optimizes the using of support material for reducing the main material usage. Furthermore, the sixteen of variation overhang angle is set to the 3D model. All models are printed into two kind of 3D printed model, printed model with support structure addition and without support addition. The weight of each 3D printed model is measured by weight scale with accuracy of tool is 10-4 g. Then the quality and the weight of 3D printed model are compared and analyzed. The result shows that the average overweight of 3D printed model with support structure addition is 40.41% than without support structure addition. Furthermore, there are several the 3D printed models without support structure that fail printed on variety model with 0° until 11° of overhang angle. The conclusion of this study is that the support structure can prevent the 3D printed model from collapsing but it does not need be built up if the overhang angle more than 11°.